2021
DOI: 10.1108/prr-08-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Saudi Arabia's economy: evidence from macro-micro modelling

Abstract: PurposeEven with the Saudi Arabian Government's discretionary measures to mitigate the spread of the coronavirus disease 2019 (COVID-19), the economic sectors were not spared from the damage. Thus, the paper aims to use a computable general equilibrium (CGE) model to evaluate the impact of COVID-19 on the Kingdom of Saudi Arabia's (KSA) economy, with a special focus on small and medium enterprises (SMEs) and production. These influence the level of poverty.Design/methodology/approachThe paper adopted the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The pandemic led to an economic downturn in many countries, including Saudi Arabia. As a result, there was a decrease in job creation, with many people becoming jobless and losing all their income or part of it [ 28 ]. Similar findings confirmed that the pandemic affected people’s employment status [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic led to an economic downturn in many countries, including Saudi Arabia. As a result, there was a decrease in job creation, with many people becoming jobless and losing all their income or part of it [ 28 ]. Similar findings confirmed that the pandemic affected people’s employment status [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Iran and KSA, like many other countries, faced various economic challenges during the pandemic that may have affected their research capacities. KSA was severely affected economically due to the radical decline in the global demand for oil, in parallel with the global economic recession, which was reflected in the sharp decline in oil prices during the first and second waves of the pandemic [ 48 ]. COVID-19 has also severely affected the Iranian economy, exacerbated by the concomitant international sanctions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia, the context of this study, places increased emphasis on economic sustainability in line with its Vision 2030 to achieve a knowledge-based economy, among other objectives [6,7]. However, like most developing economies, Saudi Arabia's major problem is its ability to meet the set developmental targets in the face of the current financial and economic crisis, which has further complicated the situation [8,9]. This development has severely affected the accomplishment of many of the relevant SDGs and had direct negative effects on economic growth, employment, poverty, and several other macroeconomic indicators.…”
Section: Introductionmentioning
confidence: 99%